Cover Picture: Two‐Dimensional Ketone‐Driven Metal–Organic Coordination on Cu(111) (Chem. Eur. J. 24/2016). Issue 24 (25th May 2016) - Della Pia, Ada; Riello, Massimo; Lawrence, James; Stassen, Daphne; Jones, Tim S.; Bonifazi, Davide; De Vita, Alessandro; Costantini, Giovanni
Abstract : The pyrene 4, 5, 9, 10‐tetraone (PTO) molecule spontaneously forms two‐dimensional metal–organic nanostructures with atoms from the substrate when deposited on a Cu(111) surface or with iron atoms if Fe is co‐deposited with PTO. The nanostructures are stabilized by the coordination of individual metallic atoms by the molecule's strongly electronegative ketone moieties. The driving force for the substitution of Cu with Fe in the metal–organic complexes is determined by the relative strengths of the ketone–metal bond. More information can be found in the Full Paper by D. Bonifazi, A. De Vita, and G. Costantini et al. onpage 8105 ff.